An intimate portrait of the individual investor - Durand, Robert; Newby, R.; Sanghani, J. (Routledge, 2008)
We examine a range of investment decisions, and ensuing portfolio performance, and establishedthat they have statistically significant associations with personality traits captured byCosta and McRae’s [1992] operationalization of Norman’s [1963] ‘Big Five’ (Negative Emotion,Extraversion, Openness to Experience, Agreeableness and Conscientiousness), Bem’s[1977] psychological gender traits (Masculinity and Femininity) and Jackson’s [1976] personalitytraits of Preference for Innovation and Risk Taking Propensity.